The Influence of Electronic Word of Mouth , Product Quality and Price Perception on Purchasing Decisions with Brand Image as an Intervening Variable (Case Study of Consumers of Jims Honey Products in Demak Regency): The Influence of Electronic Word of Mouth , Product Quality and Price Perception on Purchasing Decisions with Brand Image as an Intervening Variable (Case Study of Consumers of Jims Honey Products in Demak Regency) - Adisty, Shiella Tri; Prabowo, Heri; Violinda, Qristin (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research examines the influence of Electronic Word of Mouth, Product quality and price perception on purchasing decisions with brand image as an intervening variable for consumers of Jims Honey products in Demak Regency. This research was conducted using quantitative research methods, the research population was consumers who had purchased Jims Honey products in Demak Regency. This research used a purposive sampling technique, and took data from 138 respondents who were collected. The data collection method in this research uses a questionnaire with SEM (Structural Equation Modeling) analysis techniques on SmartPLS 3.29 software as a tool in research analysis. The research results show that electronic word of mouth, product quality and price perceptions have a positive effect on brand image . Electronic word of mouth has no effect on purchasing decisions. Product quality has a positive effect on purchasing decisions. Price perceptions have a positive influence on purchasing decisions. Brand image influences purchasing decisions . Electronic word of mouth, product quality, and price perceptions have a positive influence on purchasing decisions mediated by Brand Image